The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fcvm.2022.958259
|View full text |Cite
|
Sign up to set email alerts
|

Maximum inferior vena cava diameter predicts post-induction hypotension in hypertensive patients undergoing non-cardiac surgery under general anesthesia: A prospective cohort study

Abstract: BackgroundInferior vena cava (IVC) ultrasonography is a reliable variable that predicts post-induction hypotension (PIH) in patients undergoing surgery under general anesthesia. However, in patients with hypertension, the predictive performance of ultrasound IVC measurements needs further exploration.MethodsThis is a prospective cohort study. Adult patients with existing hypertension scheduled to undergo non-cardiac surgery under general anesthesia were eligible. An abdominal ultrasound examination was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The results of our study showed that the cutoff and age > 60 years were associated with the accuracy of the IVC-CI, and meta-regression analysis revealed a significant decrease in sensitivity for the prediction of PIH when the cutoff of the IVC-CI exceeded 50%, which was consistent with the results from previous studies [13,44]. Several studies [65][66][67] have shown that the baseline inferior vena cava (IVC) diameter varies with age, gender, weight, body mass index (BMI), and body surface area.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results of our study showed that the cutoff and age > 60 years were associated with the accuracy of the IVC-CI, and meta-regression analysis revealed a significant decrease in sensitivity for the prediction of PIH when the cutoff of the IVC-CI exceeded 50%, which was consistent with the results from previous studies [13,44]. Several studies [65][66][67] have shown that the baseline inferior vena cava (IVC) diameter varies with age, gender, weight, body mass index (BMI), and body surface area.…”
Section: Discussionsupporting
confidence: 92%
“…The IVC-CI was reported in 27 studies [12,13,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][52][53][54][56][57][58] with 2467 patients. PIH was observed in 48.03% of the patients.…”
Section: Inferior Vena Cava Collapsibility Index (Ivc-ci)mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to the current finding, Zhang and associates demonstrated poor performance of IVCCI (best cutoff value 50%) before induction in predicting hypotension after induction of GA in hypertensive patients (AUC 0.523 vs. 0.908 in the current study), while they found a comparable predictivity in normotensive patients (AUC 0.896). The different findings from the current study may be due to different sample sizes (51 vs. 153 hypertensive patients in the current study), different outcome definitions (based on MAP only in Zhang’s study vs. considering both SAP and MAP in the current study) or the state of hypertension control in the included patients (heterogenous population in Zhang study vs. controlled hypertensive patients in the current study) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%